Risk of all‐type cancer, hepatocellular carcinoma, non‐Hodgkin lymphoma and pancreatic cancer in patients infected with hepatitis B virus. Issue 10 (4th February 2015) - Andersen, E. S.; Omland, L. H.; Jepsen, P.; Krarup, H.; Christensen, P. B.; Obel, N.; Weis, N.; the DANVIR Cohort Study
Summary The increased risk of hepatocellular carcinoma (HCC) among patients infected with hepatitis B virus (HBV) is well established; however, long‐term risk estimates are needed. Recently, it has been suggested that HBV is associated with non‐Hodgkin lymphoma (NHL) and pancreatic cancer (PC). The aim of this Danish nationwide cohort study was to evaluate the association between HBV infection and all‐type cancer, HCC, NHL and PC. A cohort of patients infected with HBV (n = 4345) and an age‐ and sex‐matched population‐based comparison cohort of individuals (n = 26 070) without a positive test for HBV were linked to The Danish Cancer Registry to compare the risk of all‐type cancer, HCC, NHL and PC among the two groups. The median observation period was 8.0 years. Overall, the incidence rate ratio (IRR) for all‐type cancer among HBV‐infected patients was 1.1 (95% confidence intervals (CI) 0.9–1.3). The IRR of HCC was 17.4 (CI 5.5–54.5), whereas the IRR of PC and NHL was 0.9 (CI 0.3–2.5) and 1.2 (CI 0.4–3.6), respectively. HBV‐infected patients had a 10‐year risk of 0.24% (Cl 0.12–0.44) for HCC, whereas the comparison cohort had a 10‐year risk of 0.03% (Cl 0.02–0.07) for HCC. The risk of all‐type cancer, NHL and PC was not higher in the HBV‐infected cohort compared to non‐HBV infected. We found a 17‐fold higher risk of HCC for HBV‐infected individuals.